The semantics of " Qaswa " in the Qur'an. [In Persian] - Mehdi Rajai (International E-Research Foundation (Bonyan Pouya Pajooh Andisheh Institute), 2020)
Semantics as one of the branches of linguistics is one of the new methods in Quranic studies. Based on the Izutsu method for the semantics of words, analytical studies of the keywords of the language are carried out, and in this way the underlying worldview is revealed to those for whom the language is means of communication, and thus the semantics of the words.  Qur'an is in fact that through the words of the Qur'an, their connection with the worldview hidden in the Qur'an is realized. In this study, the semantics of "Qaswa" in the Holy Qur'an has been considered. In this study, it is concluded that this word has a relative synonym with "phrase, لظه and intensity" that these synonyms in the Qur'an in a similar context. Qaswa confirms the use of these synonyms and the relations of companionship and succession. Accordingly, this word is in conflict with "submission, obedience". Factors and words active in relation to depravity in Qur'anic expressions are "breaking the covenant, longing and being far from the truth, stubbornness and stubbornness." One of the attendants of Qaswa is Misguidance and the heart can be considered as an inseparable part of this word.  After distinguishing the words "neglect of the remembrance of God" and "heart" as key words in Quswa, the relative meaning of this word can be expressed as follows: Quswa is an adjective affecting the heart that is caused by neglecting the remembrance of God. And it indicates a kind of intensity and difficulty.